TREATMENT ADHERENCE OF COVID-19 PATIENTS GETTING MEDICATION AT HOME - Önder Porsuk, Ahmet; Cerit, Çiğdem (Sanamed, 2022)
Introduction: Turkey has adopted outpatient treatment of COVID-19 since the beginning of the pandemic. In the outpatient treatment of COVID-19 in Turkey, only hydroxychloroquine was initially used, favipiravir was added to the treatment, and finally, hydroxychloroquine was removed from the treatment and only favipiravir was used. Our study aims to examine the adherence to the recommended treatment of people diagnosed with COVID-19 who have received outpatient treatment without hospitalization and their attitudes and declared behaviors towards using the medications they were given free of charge. Methods: This follow-up study was conducted between February 15, 2021, and May 15, 2021, by telephone survey method in the Lüleburgaz District of Kırklareli City. The study participants were 4368 people who were diagnosed with COVID-19 with a positive PCR test in Lüleburgaz District between February 15 and May 15, 2021, and were given hydroxychloroquine and/or favipiravir drugs for home use after being deemed suitable for outpatient treatment according to the guidelines of the Republic of Turkey Ministry of Health. Results: 88.1% (n=3849) of the survey respondents reported using the given medications regularly, while 11.9% (n=519) did not use them regularly. The most important socio demographic factor affecting the regular use was age, and the patient-centered factor was the sense of trust. Conclusion: In the fight against COVID-19, measures to increase the sense of trust of patients who are expected to adhere to the treatments should be considered a priority.